Policy support in promoting green bonds in Asia - Dina Azhgaliyeva; Zhanna Kapsalyamova (Asian Development Bank Institute (ADBI), 2021)
Private green finance is imperative for climate change mitigation and adaptation, but the share of private green finance remains small, and the studies that have tackled the efficacy of policy instruments in promoting green finance are limited. Many economies, especially in Asia, have implemented different policies to incentivize the private sector to issue green bonds. However, there is a lack of empirical evidence on the effectiveness of such policies. To date, this is the first study to provide empirical evidence on the effectiveness of a broad range of green bond policies on the issuance of green bonds. Given the nascent nature of green bonds, this paper documents the effects of several policy instruments supporting green bonds on the private sector's issuance of green bonds in 58 green-bond-issuing economies, including 11 economies in Asia, over the period January 2010−June 2020. Using the difference-in-difference specification within the multilevel longitudinal model, the paper finds that some green bond policies, such as green bond grants and tax incentives, as well as cooperation and policy signals, are effective in promoting the issuance of green bonds in the private sector in Asia. Regional cooperation and standardization have incentivized private green bond issuance in the European Union but not in the Association of Southeast Asian Nations region. Global cooperation and international standardization have had a positive impact on the issuance of private green bonds.
Keywords: Q28; Q42; Q48; G23; 330; green bonds; green finance; policy support; Asia